EFFORTS TO IMPROVE LEARNING ACHIEVEMENT ON SOCIAL SCIENCES SUBJECT BY APPLYING ROLE PLAYING METHOD AT GRADE V OF ELEMENTARY SCHOOL - Eufrasia Jeramat; Sufantiara Naming; Valeria Suryani Kurnila; Mikael Nardi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to improve students’ learning achievement on social science subject at grade V of SD Wae Rii by applying role playing method. The research was conducted in elementary schools Kecamatan Wae Rii Langke Rembong in the academic year 2019/2020. The method was classroom action research design and McTaggart Kemmis consisting of three phases: planning, action and observation stage, and the stage of reflection. The subjects were 30 students at grade V of SD Wae Rii. Data were collected through observation and tests. The instrument of this study were observation sheets and test questions. The results showed that role playing method improved the students’ learning achievement on social science subject at grade V SD Wae Rii. The increase was evident from that many students achieved a minimum completeness criteria (KKM). In pretreatment, 8 students achieved KKM (40%); in cycle I 14 students reached the KKM (70%), in cycle II it increased to 17 students who reached the KKM (85%). Based on data analysis, it was concluded that role playing method improved students’ learning achievement on social science subject at grade V of SD Kecamatan Wae Rii Langke Rembong the Academic Year 2019/2020